The Use of Acronym Strategy to Teach Descriptive-Text Writing toward English-Majored University Students - Putra, Octa; Endry Boeriswati; Ratna Dewanti (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Writing is often regarded as the most challenging English skill compared to speaking, listening, and reading. Despite students having access to online tips and strategies, writing difficulties—especially in composing descriptive paragraphs—remain unresolved, as reflected in their low scores. This pre-experimental research aims to examine the effectiveness of using acronyms as a guideline in teaching descriptive writing. The study involved English-major university students at Bina Sarana Informatika, Jakarta, Indonesia. Data analysis focused on the frequency and percentage of students’ pre-test and post-test scores. Results revealed that, in the pre-test, 30% (9 students) were in the "poor" category and 43.33% (13 students) in the "fair" category. In the post-test, 60% (18 students) reached the "fairly good" category, while 16.67% (5 students) were in the "good" category. These findings indicate a significant improvement in students’ writing abilities. The t-test result exceeded the t-table value, confirming that the acronym-based writing strategy effectively enhances students’ descriptive writing skills.